2016
DOI: 10.4110/in.2016.16.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Ambroxol on Airway Hyperresponsiveness and Inflammation

Abstract: Ambroxol is used in COPD and asthma to increase mucociliary clearance and regulate surfactant levels, perhaps through anti-oxidant and anti-inflammatory activities. To determine the role and effect of ambroxol in an experimental model of asthma, BALB/c mice were sensitized to ovalbumin (OVA) followed by 3 days of challenge. Airway hyperresponsiveness (AHR), lung cell composition and histology, and cytokine and protein carbonyl levels in bronchoalveolar lavage (BAL) fluid were determined. Ambroxol was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…It also has anti-inflammatory and anti-oxidant [3, 4] and anti-bacterial and anti-viral properties [2, 5]. Recently, ambroxol was shown to also exhibit immunomodulatory effects in a murine asthma model, where it normalized airway hyperresponsiveness and reduced eosinophils and Th2-related cytokines in bronchoalveolar lavage [6]. Finally, ambroxol affects lysosomal function, which may be beneficial in lysosomal storage diseases [7] or Parkinson’s disease [8], but the relevance of this finding remains to be tested clinically.…”
Section: Introductionmentioning
confidence: 99%
“…It also has anti-inflammatory and anti-oxidant [3, 4] and anti-bacterial and anti-viral properties [2, 5]. Recently, ambroxol was shown to also exhibit immunomodulatory effects in a murine asthma model, where it normalized airway hyperresponsiveness and reduced eosinophils and Th2-related cytokines in bronchoalveolar lavage [6]. Finally, ambroxol affects lysosomal function, which may be beneficial in lysosomal storage diseases [7] or Parkinson’s disease [8], but the relevance of this finding remains to be tested clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, overall this had a beneficial and protective effect. 285 This applies similarly to IL5, which has a positive chemotactic action on eosinophilic granulocytes: Sturgill et al 287 also demonstrated a reduction of IL5 in FMS. Ambroxol also has an inhibiting effect concerning IL5, and if administered prior to provocation in an animal model, suppressed hyperreactivity and airway eosinophilia and reduced inflammation of subepithelial regions.…”
Section: Inflammatory Mediatorsmentioning
confidence: 90%
“… 87 Following exposure to allergens in an artificially sensitized respiratory tract in an animal model, however, ambroxol induced an increase in IL10 in a “protective” manner. 285 …”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A co-aerosolized, DPPC-ambroxol intervention may present a synergistic outcome in ARDS intervention at early stages and may be a potential clinical trial candidate for COVID-19 as it may essentially provide with alleviation of the inherent inflammatory response, attenuation of epithelial cell damage, decreased interstitial exudation and edema, and hence reduced lung damage. When co-administered, ambroxol may act by reducing the inflammation (Takeda et al, 2016;Kanie et al, 2017) which in turn may minimize the pulmonary capillary permeability thereby affecting the edema blebs (Figure 1). Concurrently, the exogenous surfactant delivered to the lungs may replenish the deactivated surfactant and hence the surfactant lining will be restored.…”
Section: The Hypothesis and The Discussionmentioning
confidence: 99%